2013
DOI: 10.1002/prep.201200199
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Insensitive HMX/Graphene Oxide Composites

Abstract: To improve the safety of HMX, a two‐dimensional (2D) graphene oxide (GO) was introduced to HMX by the solventnonsolvent method. The morphology, composition, thermal decomposition characteristic were characterized by scanning electron microscopy (SEM), X‐ray diffraction (XRD), X‐ray photoelectron spectroscopy (XPS), thermogravimetry (TG) and differential scanning calorimetry (DSC). Compared to the previous reports, GO sheets exhibited better desensitizing effect than [60]Fullerene and CNTs. When 2.0 wt‐% GO sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(45 citation statements)
references
References 60 publications
0
45
0
Order By: Relevance
“…A larger P indicated higher sensitivity. 28 The sensitivity results for the samples are listed in Table 1. Furthermore, to provide a rough estimate of the desensitizing effect of rGO and G, the mechanical sensitivities of HMX/[60]fullerene and HMX/carbon nanotubes (CNTs) are summarized in Table 1.…”
Section: Sensitivity Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…A larger P indicated higher sensitivity. 28 The sensitivity results for the samples are listed in Table 1. Furthermore, to provide a rough estimate of the desensitizing effect of rGO and G, the mechanical sensitivities of HMX/[60]fullerene and HMX/carbon nanotubes (CNTs) are summarized in Table 1.…”
Section: Sensitivity Analysismentioning
confidence: 99%
“…20,21 Examples of these nanomaterials include insensitive HMX/GO composites, surface-coated insensitive HMX with Viton and GO, HMX coated with graphene oxide by electrostatic self-assembly, graphene nanoplatelet-lead styphnate composites with depressed electrostatic hazards, CL-20 hosted in graphene foam, and insensitive 3-HNIW with binders and graphite. [22][23][24][25][26][27][28] Some of the most important research focus is graphene nanomaterials, which can be utilized as carriers of energetic components via coating or encapsulation. The graphene-coated or graphene-encapsulated energetic components can form advanced nanostructures with superior performance, thus improving the safety of energetic systems.…”
Section: 5-10mentioning
confidence: 99%
“…19). 168 In a typical procedure, HMX was dissolved in DMF at 40°C and then GO (about 2 wt%) was added. After GO was completely dispersed in HMX solution in DMF by sonication, the mixture was injected into CH 2 Cl 2 (in which GO is much less soluble).…”
Section: Ems Based On Go and Rgomentioning
confidence: 99%
“…As the successful preparation of nano-sized nitramine explosives (RDX, HMX), the properties of the explosives have been greatly improved [28][29][30], and the application of nano-sized explosives is also expanding. However, previous studies have shown that charge accumulation is inversely proportional to the particle size of explosives [3].…”
Section: Introductionmentioning
confidence: 99%
“…The main content of this paper consists of three sections: the resistivity test, the charging characteristics test, and the ESD sensitivity test. Micron-sized RDX (China military standard GJB296A-1995 with purity of 99.5%) and micron-sized HMX (China military standard GJB2335-1995 with purity of 99.5%), produced by Gansu Yinguang Chemical Industry Group Co., Ltd. of China, were ground into several different particle sizes by the National Special Superfine Powder Engineering Research Center of China using a bidirectional rotation mill [30]. We neglected the influence of antistatic agents (if they existed in the impurities) on the samples.…”
Section: Introductionmentioning
confidence: 99%